Estrategias mediadoras de conflictos escolares, y su incidencia en la convivencia educativa de los estudiantes de la unidad educativa “Adolfo María Astudillo” del cantón Babahoyo, provincia los Ríos - Bedòn Vera, Tatiana Mariuxi (2017)
Through the elaboration of this work, it has been possible to recognize some actions that enable the capacities and competencies of all the members of the school community to be implemented for the implementation of a culture of peace and coexistence in basic education, mainly in secondary education, as well know how to act Keep in mind that trying to improve school life is not the work of a single person or teacher, even if a teacher has all the skills and competences an isolated work does not affect the overall education of the student, therefore encourage or teach to live in school is a function of the whole group and the school community, empowering everyone around the culture of integral peace. The mediating strategies of conflicts contribute to progress the educational coexistence among the students of the institution, the education is a continuous change where the students must achieve an integral and formative development that helps to socialize with the people that surround them. The institutions of today are not always the space of coexistence desired for our children, in it the curricular and non-curricular influence are established and planned in order to develop and build values of coexistence, solidarity and dialogue among the subjects. The importance that will be given to school conflicts to improve educational coexistence is through mediating strategies of conflicts that will contribute as much as possible to build friendship links among the students of the Educational Unit "Adolfo María Astudillo del Cantón Babahoyo Province of Los Ríos, they are especially designed for the higher grades and are given in the educational field, as well as in daily life, since their values will help in personal and school growth.